The Relationship Between Personal Hygiene and Soil Transmitted Helminths in Students of State Elementary School Inpres 1 Apo, Jayapura City - Hukubun, Mersi Diana; Irjayanti, Apriyana; Pamangin, Lisda Oktavia; Ilmidin, Ilmidin (Lambung Mangkurat University, 2026)
Soil Transmitted Helminths (STH) remains a health problem found in tropical countries, especially Indonesia, where humidity supports the development of worm parasites. This study aimed to determine the relationship between personal hygiene and worm infections among students of SD Negeri Inpres 1 Apo, Jayapura City. This analytical observational study used a cross-sectional design with a population of 167 and a sample of 97 respondents selected through proportionate stratified random sampling. Inclusion criteria were fifth and sixth grade students willing to participate and submit faecal samples; absent or sick students were excluded. Data were collected using questionnaires and faecal examinations through the direct method at the Jayapura Health Polytechnic Laboratory. Data were analysed using univariate and bivariate analysis with the chi-square test (α < 0.05). Results showed that most respondents were 11 years old (45.4%), female (55.7%), class VI B students (24%), and 47.4% tested positive helminth infection. Bivariate analysis found no significant relationship between knowledge, handwashing, footwear use, nail hygiene, snack hygiene, or defecation habits and helminth infection (p > 0.05). Although no significant association was found, good personal hygiene remains essential to prevent STH. Education from schools and parents is crucial to improve children’s hygiene practices.